American buyers : demographics of shopping (Money Series., 2012)
Based on data collected from the Bureau of Labor Statistics, this guide presents 2010 weekly and quarterly spending data to help businesses analyze buying patterns, manage expectations, and set prices. It features the percentage of households that buy individual products and services and how much buyers pay for them, all organized by demographics.